2021
DOI: 10.3390/rel12111026
|View full text |Cite
|
Sign up to set email alerts
|

To Heaven through Hell: Are There Cognitive Foundations for Purgatory? Evidence from Islamic Cultures

Abstract: The purgatory doctrine, which has played a vital role in Christian culture, states that most believers must experience afterlife punishment in order to be cleansed of their sins before entering Heaven. Traditional Islamic theology rejects the notion of purgatory (Al-Motahher) through the Balance doctrine (Mizan), which states that if the good deeds performed during a Muslim’s life outweigh their bad deeds, the person will enter heaven without suffering or punishment. This study hypothesizes that folk intuition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…One of the obstacles that hinders a deeper understanding of this phenomenon is the lack of empirical studies that examine how Muslims perceive afterlife beliefs (Al-Issa et al 2021a). A recent study by Al-Issa and his colleagues (Al-Issa et al 2021b) suggests that this misunderstanding may arise as a result of cognitive bias, as researchers have found that some Muslims believe that it is imperative that one enters Hell to be cleansed of her/his sins before entering Paradise, even if their good deeds outweigh their bad ones. This belief contradicts the official theological doctrine of all orthodox Islamic theological sects.…”
Section: General Discussion and Directions For Future Researchmentioning
confidence: 99%
“…One of the obstacles that hinders a deeper understanding of this phenomenon is the lack of empirical studies that examine how Muslims perceive afterlife beliefs (Al-Issa et al 2021a). A recent study by Al-Issa and his colleagues (Al-Issa et al 2021b) suggests that this misunderstanding may arise as a result of cognitive bias, as researchers have found that some Muslims believe that it is imperative that one enters Hell to be cleansed of her/his sins before entering Paradise, even if their good deeds outweigh their bad ones. This belief contradicts the official theological doctrine of all orthodox Islamic theological sects.…”
Section: General Discussion and Directions For Future Researchmentioning
confidence: 99%
“…Clinicians treating Muslim patients living with ADRD must recognize the profound influence of Islamic beliefs on perceptions and care practices related to this condition. Many Muslims believe that good deeds will be rewarded, and bad deeds punished, often after one’s earthly existence, though not necessarily [ 39 ]. However, illnesses and diseases such as ADRD are not viewed as punishments for spiritual failures, but rather as biological processes, albeit abnormal [ 40 ].…”
Section: Islamic Perspectives On Adrdmentioning
confidence: 99%
“…Many concepts in religion are not properly comprehended. For example, proportionality and immanent justice biases are not something foreign or unique; theological incorrectness can be seen in Muslim societies concerning the concept of Mizan (literal translation: balance) (see Al-Issa, Krauss, Roslan, & Abdullah, 2021), which needs to be addressed, as part of an Islamic worldview.…”
Section: Constructs Identified Through a Narrative Analysismentioning
confidence: 99%